Dielectric Studies on Fe3O4 Nanodoped p-n-Alkyloxybenzoic Acids. (16th June 2014) - Sastry, S. Sreehari; Kumar, L. Tanuj; Vishwam, T.; Murthy, V. R. K.; Lakshminaryana, S.; Sie Tiong, Ha
Abstract : The stability of phase transition temperatures and textural changes for thermotropic pure and nanodoped p -n -alkyloxybenzoic acid mesogens were aimed to study at considerable time periods. Frequency and temperature dependent dielectric constant and dielectric loss for the pure and nanodoped liquid crystals were carried out. Significant anomalies in dielectric studies were observed near phase transitions when dielectric constant and dielectric loss had been measured as a function of temperature and frequency. Changes in dielectric constant and loss were observed and there were no apparent changes at high frequencies instead maintaining constant values. The variations in conductivity, activation energy, and relaxation times had also been studied in the nematic and smectic phases. The temperature dependent dielectric constant stability (temperature coefficient of dielectric constant τ ε ) had shown shift in the observed frequency range of thermotropic liquid crystals corresponding to the change in the dielectric constant values.